Girls in STEM: Is It a Female Role-Model Thing? - González-Pérez, Susana; Mateos de Cabo, Ruth; Sáinz, Milagros (Frontiers in Psychology, 2020)
Women are underrepresented in STEM careers, and this poses new challenges at the dawn of the era of digital transformation. The goal of the present study is to demonstrate how female role models influence girls’ preferences for STEM studies. We evaluate a role model intervention, where female volunteers working in STEM go into schools to talk to girls about their careers. We conducted a study with 304 girls, from 12 years old (6th primary grade) to 16 years old (4th secondary grade), before and after the role-model sessions. We use an adaptation of the expectancy-value of achievement motivation theory to test the extent to which this role model intervention improves girls’ beliefs that they can be successful in STEM fields and increases their likelihood of choosing a STEM career. The results of the multigroup SEM analysis showed that, at the mean level, the role model intervention had a positive and significant effect on math enjoyment, importance attached to math, expectations of success in math, and girls’ aspirations in STEM, and a negative effect on gender stereotypes. Additionally, the female role-model sessions significantly increased the positive impact of expectations of success on STEM choices. Finally, the moderation role of the no stereotypical content of the role model sessions was also tested. Results show that the higher the no stereotypical character of the sessions, the higher the relationship between expectations of success in math and the choice of STEM. These results are discussed regarding their implications for long-term STEM engagement.